Analisis black site dan black spot serta faktor-faktor yang mempengaruhi kecelakaan lalu lintas di Kabupaten Klungkung, Provinsi Bali - I Made Agus Ariawan; I Putu Chandra Wibawa; I Nyoman Arya Thanaya; Marshal Riando Samosir (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2025)
The rapid population growth in Klungkung Regency, accompanied by an increase in motor vehicle ownership, has accelerated the development of transportation in the region. Although traffic density in Klungkung is lower than that in larger cities, traffic accidents continue to occur. Therefore, identifying accident-prone areas and the contributing factors is essential. This study aims to analyze black sites and black spots, as well as to identify the factors influencing traffic accidents in Klungkung Regency. The research utilizes secondary data obtained from the Klungkung Police Department. The analysis begins with problem identification, data collection, and the application of Z-Score and Accident Equivalent Number (AEK) methods to identify black sites. Black spots are identified using the Upper Control Limit (UCL) method, followed by an analysis of accident-contributing factors. The findings reveal that 79.3% of accidents involve motorcycles, with an estimated economic loss of IDR 646,725,000. The dominant type of accident (44.71%) is loss of vehicle control, while 23% of incidents occur on Sundays, and 32.23% of the offenders are between 16 and 25 years old. Four black sites were identified: Prof. Dr. Ida Bagus Mantra Road, Raya Sampalan Road, Ngurah Rai Road, and Raya Klumbu Tokah Pakeh Road. In addition, six black spots were found: STA 0+000–0+500, STA 2+000–2+500, STA 3+000–3+500, STA 4+000–4+500, STA 5+000–5+500, and STA 7+000–7+500. Contributing human factors include careless behavior, drowsiness, sudden braking, and mobile phone use while driving. Vehicle-related causes involve brake failure, faulty lights, worn tires, and missing mirrors. Accidents are more likely to occur under clear weather conditions due to a reduced perception of risk, which can lead drivers to lower their vigilance and violate traffic regulations. This study offers an integrated analytical approach to identifying black sites and black spots while examining key accident factors. The findings are expected to support targeted strategies and serve as a reference for policymakers and traffic safety authorities in developing more effective prevention measures.